Multiple sclerosis in pregnancy: prevalence, sociodemographic features, and obstetrical outcomes. (1st February 2018) - Fong, Alex; Chau, Cindy T.; Quant, Cara; Duffy, Jennifer; Pan, Deyu; Ogunyemi, Dotun A.
Abstract: Objective: We sought to describe the prevalence, sociodemographic features, and antenatal/peripartum outcomes of multiple sclerosis (MS) in pregnancy. Study design: A retrospective cohort study was performed using deliveries in California from 2001 to 2009. Cases of MS as well as other morbidities were identified via ICD-9-CM code. Logistic regression was performed to adjust for potential confounders. Results: About 1185 out of 4, 424, 049 deliveries were complicated by MS. MS prevalence increased with maternal age, with Caucasians comprising a higher proportion of MS subjects. MS subjects were older and more likely to have private insurance. Women with MS were more likely to have preexisting medical conditions such as asthma, chronic hypertension, thyroid disease, or cardiac disease. However, no significant antepartum and peripartum morbidities were found to be increased in patients with MS. Urinary tract infection, cesarean delivery, and induction of labor were slightly increased in MS patients. Conclusions: MS is a rare condition which is more likely to affect older Caucasian women of higher socioeconomic status and is associated with several preexisting medical conditions. MS, however, does not appear to pose significant increases in adverse pregnancy outcome. This suggests that pregnant patients with MS may likely experience an uneventful pregnancy.